Perubahan Status Hemodinamik Pada Pasien Open Pneumothorax dengan Implementasi Pemasangan Occlusive Bandage di Instalasi Gawat Darurat: A Case Report - Billa, Mutia Salsa; Subandi, Andi (FORIKES, 2025)
Open pneumothorax occurs due to a stab wound to the chest wall and penetrates the chest cavity. The wound remains open (sucking chest wound). Open pneumothorax cases require immediate wound closure with an occlusive bandage as a temporary measure. The purpose of this study was to discuss emergency management by observing changes in hemodynamic status in patients with open pneumothorax after the implementation of an occlusive bandage. This study was a case report on a single patient. The case was selected due to a rare emergency situation. The patient was given an occlusive bandage. The results showed that the patient was a 24-year-old man who presented with a stab wound to the left chest due to being stabbed with a knife. Signs of respiratory distress were found. Left chest wall movement was delayed, there was a sucking chest wound on the left side, decreased breath sounds on the left side, and a hyperresonant left chest. Physical examination findings included blood pressure 80/43 mmHg, heart rate 106 beats/min, respiratory rate 25 beats/min, SpO2 92%, temperature 36.1°C, Glasgow coma scale 15. A chest X-ray revealed a left pneumothorax, while laboratory results were within normal limits. In the emergency department, a modified occlusive bandage made of plastic, cut to size, was applied and taped on three sides. Following the occlusive bandage, hemodynamic status improved, allowing for definitive intervention and further management. It was concluded that the application of an occlusive bandage can improve the patient's hemodynamic status, making it important to implement this procedure before definitive intervention.Keywords: open pneumothorax; sucking chest wound; occlusive bandage ABSTRAK Open pneumothorax terjadi akibat luka tusuk pada dinding dada dan menembus rongga dada. Luka tersebut tetap terbuka (sucking chest wound). Kasus open pneumothorax memerlukan penutupan luka segera dengan occlusive bandage yang merupakan pertolongan sementara. Tujuan dari studi ini adalah mendiskusikan tatalaksana emergency dengan mengobservasi perubahan status hemodinamik pada pasien open pneumothorax setelah implementasi pemasangan occlusive bandage. Studi ini merupakan laporan kasus pada satu pasien. Kasus dipilih dalam status emergency yang jarang terjadi. Pasien diberikan implementasi pemasangan occlusive bandage. Hasil studi menunjukkan bahwa pasien merupakan lelaki berusia 24 tahun yang datang dengan luka tusuk pada dada kiri akibat ditusuk dengan pisau. Ditemukan tanda-tanda gangguan pada breathing. Pergerakan dinding dada kiri tertinggal, ada sucking chest wound sisi kiri, penurunan suara nafas di sisi kiri, dan dada kiri hipersonor. Hasil pemeriksaan fisik adalah tekanan darah: 80/43 mmHg, hearth rate: 106x/min, respiratory rate: 25 kali/min, SpO2: 92%, suhu: 36,10C, Glasgow coma scale: 15. Pemeriksaan rontgen toraks menunjukkan kesan pneumothorax kiri, sedangkan hasil pemeriksaan laboratorium dalam batas normal. Di unit gawat darurat dilakukan pemasangan occlusive bandage yang dimodifikasi dari plastik dan dipotong sesuai ukuran, lalu diplester pada 3 sisi. Setelah pemasangan occlusive bandage terdapat perbaikan status hemodinamik, sehingga dapat dilakukan tindakan definitif dan penanganan lebih lanjut. Disimpulkan bahwa pemasangan occlusive bandage dapat meningkatkan status hemodinamik pasien, maka tindakan ini penting diimplementasikan sebelum tindakan definitif. Kata kunci: open pneumothorax; sucking chest wound; occlusive bandage